Pengaruh Dimensi Atom Target D.C. Magnetron Sputtering Terhadap Sifat Mekanis Baja AISI 410 - Gaguk Jatisukamto (Jurnal Energi dan Teknologi Manufaktur, 2018)
Micro machining technology uses AISI 410 steel as tools and surgical equipment. AISI 410 steel is hardenable so it is relatively easy to repair its mechanical properties. The weakness of heat treatment in AISI 410 steel for small dimensioned components causes distortion. Therefore, in this research, an effort to improve the mechanical properties of AISI 410 steel using physical vapor deposition (PVD) technique. The method of this research is to deposition Ti-N, Cr-N, W-N and Al-N with D.C magnetron sputtering technique. The sputtering process is carried out at room temperature by bombarding the target material (coating) with Argon gas, so that the bombed atoms will be deposited on the surface of the substrate (coated material). The results showed that the film layer deposition properties on the surface of AISI 410 steel were influenced by the characteristics of the formed nitride layer and the size of the atoms that struck the surface of AISI 410 steel.